ENVIRONMENTAL EDUCATION: PEDAGOGICAL PRACTICE AND ITS APPLICATION IN PUBLIC SCHOOL (Fiep Bulletin - online, 2020)
The school is a privileged space that allows the individual the formation of values ??through knowledge and the teacher has a fundamental role in building with his students a sustainable awareness of the environment. The aim of this paper was to analyze the pedagogical practices applied by the teachers of two public state schools located in the municipalities of Capim Branco and Prudente de Morais, MG, in order to verify how often the environmental theme is worked in the classrooms. as well as whether there is ease and understanding in working interdisciplinarily on environmental issues with the disciplines that teachers teach and whether teaching resources (books, games, technologies) are available to teachers to work on such a topic. A structured and adapted questionnaire was elaborated and adapted to the PE and Middle teachers, composed of multiple choice and dichotomous questions and the information obtained was analyzed. There was little frequency in working with environmental themes in the disciplines that teachers teach and even in the face of difficulties in obtaining didactic resources to work with this theme in public schools, teachers are stimulated and develop pedagogical practice beyond the traditional, However, they contradict each other by supporting Environmental Education as a curricular discipline, which shows a lack of theoretical basis on Environmental Education.
Keywords: Environmental Education; Interdisciplinary; Pedagogical Practice.